Alkali-activated grouts with incorporated fly ash: From NMR analysis to mechanical properties. (March 2018) - Cherki El Idrissi, Anass; Paris, Michaël; Rozière, Emmanuel; Deneele, Dimitri; Darson, Sabine; Loukili, Ahmed
Abstract: The nanostructure of alkali-activated materials is now better understood. However, very few studies have been carried on grouts. These highly diluted systems are used to improved soil properties for instance. In this study, the evolution of their local structure was monitored via 29 Si and 27 Al NMR to understand the formation of the binding phase and its evolution at long-term. The results of this analysis were used to question the relationship between the evolution of the chemistry of binding phases and the observed changes in the mechanical properties at material scale. Metakaolin and slag were used, with the partial incorporation of fly ash to study its effects and the potential benefits of its use. The results show that while metakaolin-based systems are very stable at both scales (local and macroscopic), the structure of slag-based grouts tends to evolve, with a negative impact on their mechanical performance.